Kingdom of the Netherlands-Netherlands : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This Netherlands's 2005 Article IV Consultation reports that raising participation and productivity are important for boosting the economy potential and reducing pressures on the public finances in the face of population aging. The authorities have implemented or are in the process of implementing key reforms, including by tightening disability and unemployment benefits and early retirement arrangements, lessening inactivity traps, enhancing competition, and reducing the administrative burden. The financial system remains sound, resilient to potential adverse shocks, and well supervised.